Forest Bird Diversity in Four Buffer Villages of Gandang Dewata National Park, Mamasa Regency, West Sulawesi, Indonesia - Yulianto, Yusuf; Nurhidayah; Nurdin, Muh Rizaldi Trias Jaya P; Putera, Alexander Kurniawan Sariyanto (Indonesian Journal of Ecology and Conservation, 2024)
A study on the diversity of forest birds in four villages serving as buffer zones of Gandang Dewata National Park has been conducted. This research aimed to determine the level of forest bird species diversity in these four villages. The study was carried out in four villages, namely Taupe Village, Tondok Bakaru Village, Mambulling Village, and Rambusaratu Village. The point count method was used to collect bird observation data. Data analysis included the Shannon diversity index, abundance index, dominance index, evenness index, species richness index, and species similarity index. The results showed that a total of 27 species of forest birds were recorded across the four villages. The number of individuals recorded in each village was as follows: Taupe Village (Station 1) with 7 species and 41 individuals, Tondok Bakaru Village (Station 2) with 11 species and 92 individuals, Mambulling Village (Station 3) with 12 species and 88 individuals, and Rambusaratu Village (Station 4) with 9 species and 211 individuals.